Anaerobic Digestion of Fruit Waste Mixed With Sewage Sludge Digestate Biochar: Influence on Biomethane Production - Ambaye, Teklit Gebregiorgis; Rene, Eldon R.; Dupont, Capucine; Wongrod, Suchanya; van Hullebusch, Eric D. (Frontiers in Energy Research, 2020)
The main aim of this study was to evaluate the biomethane potential (BMP) of fruit waste by incorporating additives such as sewage sludge biochar at different inoculum-to-substrate ratios (ISRs) of 2, 1.5, and 1 (wt./wt.). The results showed an improvement in the maximum methane production by 13, 20, and 27% upon the addition of sewage sludge biochar produced at 350°C for ISR of 2, 1.5, and 1 (wt./wt.), respectively, and an increase 12, 18, and 22% for the added biochar produced at 550°C for ISR of 2, 1.5, and 1 (wt./wt.), respectively, compared to the BMP tests performed without the addition of biochar (i.e., the control). Biochar addition reduced volatile fatty acid (VFA) formation during the digestion of fruit waste as compared to the control reactor, which is a strong indication that the metabolic process of the system was streamlined to methanogenesis. The maximum methane yield for the tested fruit substrates was 285.7 mL CH4/g in the presence of biochar prepared at a low temperature (350°C). This value is higher than one obtained with same amount of biochar prepared at a higher temperature (550°C). The results from this study showed that the effectiveness of the anaerobic digestion process depends on the ISR, biochar dose, and the pyrolysis temperature used for the production of the sewage sludge digestate biochar.